2016
DOI: 10.1039/c6cc06752b
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable catalysis of a wool-like copper electrode for NH3 synthesis from N2 and H2 in non-thermal atmospheric plasma

Abstract: A wool-like copper electrode used to produce non-thermal plasma functioned as an efficient catalyst for ammonia production from N and H under atmospheric pressure without heating. The catalytic activity increased as the experiments were repeated. The yield of ammonia at H/N = 3 was 3.5%. The intensity of the emission spectra of N*(C-B) bands was correlated with the ammonia synthesis rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 31 publications
2
103
1
Order By: Relevance
“…This conclusion is in line with many previously reported researches [110][111][112][113][114]. On the other hand, other studies have shown that a higher N 2 /H 2 is favoured for the ammonia production [107,112,[115][116][117][118][119]. A plausible explanation for this difference was given by Peng et al [120], who believes that the average electron density and temperature is higher in a high hydrogen content environment with less intensive discharges (low voltage and frequency), promoting the formation of NH radicals, hence resulting in high ammonia productions.…”
Section: Direct Synthesis Of Ammonia From N 2 and Hsupporting
confidence: 92%
“…This conclusion is in line with many previously reported researches [110][111][112][113][114]. On the other hand, other studies have shown that a higher N 2 /H 2 is favoured for the ammonia production [107,112,[115][116][117][118][119]. A plausible explanation for this difference was given by Peng et al [120], who believes that the average electron density and temperature is higher in a high hydrogen content environment with less intensive discharges (low voltage and frequency), promoting the formation of NH radicals, hence resulting in high ammonia productions.…”
Section: Direct Synthesis Of Ammonia From N 2 and Hsupporting
confidence: 92%
“…Ru catalyst with CNT support outperformed the others, where cesium acted as a promoter, and Molecular Sieve 13X and Amberlyst 15 served as microporous absorbents [168]. Iwamoto and colleagues [169] designed a wool-like copper electrode, which was found to be an effective catalyst for NH 3 synthesis, using nonthermal atmospheric-pressure plasma by glow discharge. The energy efficiency of NH 3 production reached 3.5% with an NH 3 production rate of 3.3 g NH 3 /kWh.…”
Section: Plasma Catalysis For Ammonia Productionmentioning
confidence: 99%
“…[76][77][78] In addition to exploring the effects of the above-mentionedc atalysts, the authors also discussed the mechanisms of the fundamentaln onthermalp lasma-assisted ammonia synthesis based on ap roposal by Carrasco et al, [79] who stated that the plasma-assisted ammonia synthesis under vacuum occurs mainly through the ER and Langmuir-Hinshelwood (LH) mechanisms (they described the interactions between surface-adsorbed and gasphase speciesa nd the interactions betweent wo surface-adsorbed species, respectively). [77] Iwamoto et al [80] and Aihara et al [81] also compared the catalytic activities of different single-metal catalysts (Fe, Cu, Pd, Ag, etc.) [77] Iwamoto et al [80] and Aihara et al [81] also compared the catalytic activities of different single-metal catalysts (Fe, Cu, Pd, Ag, etc.)…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%
“…[67,79] Based on this, Shah further demonstrated that the electron temperature is the main factor controlling N 2 dissociation in the gas phase. [77] Iwamoto et al [80] and Aihara et al [81] also compared the catalytic activities of different single-metal catalysts (Fe, Cu, Pd, Ag, etc.) under atmospheric dielectric barrier discharge conditions.…”
Section: Plasma-catalyst Interactionsmentioning
confidence: 99%